Improved ð‘«âˆ’ð‘¯ð’† ðŸ‘ Fusion Reaction Characteristics Parameters - Taki, Ali K.; Majeed, Raad H.; Jassim, Mustafa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The most likely fusion reaction to be practical is Deuterium and Helium-3 (ð·âˆ’ð»ð‘’ 3 ), which is highly desirable because both Helium -3 and Deuterium are stable and the reaction produces a 14 ð‘€ð‘’ð‘‰ proton instead of a neutron and the proton can be shielded by magnetic fields. The strongly dependency of the basically hot plasma parameters such as reactivity, reaction rate, and energy for the emitted protons, upon the total cross section, make the problems for choosing the desirable formula for the cross section, the main goal for our present work.